2015
DOI: 10.21863/jem/2015.4.3.012
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Different Leadership Styles of CEOs on Business Performance of SMEs in East Africa: A Systematic Review of Literature

Abstract: This study attempts to review the prevailing body of literature on impacts of CEOs different leadership styles on business performance of SMEs in East Africa. The objective of this study is to identify the research trend in the area and issues that are currently addressed in East Africa so as to help interested researchers in the area. 130 relevant studies on the topic were systematically reviewed and the findings showed that, Asia has the leading number of studies published consistently within the past ten ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…As a result of such campaigns, Tanzania is mentioned among countries with a greatest segment of people employed in the informal sector in comparison to other countries in Africa (ILO, 2015;Mori, Kazungu & Panga 2015;Dell'Anno, AnaMaria & Balele, 2018;Munishi & Casmir, 2019;Munishi & Kirumirah, 2020a;Munishi & Kirumirah, 2020b). Evidence further shows that, the informal sector has played and still plays major role of employment and earnings for rapidly growing populations adding that from 1985 to 2010, the population bracket of 15-24 years of age doubled in the African and as a result urban informal trade almost tripled thanks to the less cumbersome regulations and taxation (Mgeni & Nayak, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…As a result of such campaigns, Tanzania is mentioned among countries with a greatest segment of people employed in the informal sector in comparison to other countries in Africa (ILO, 2015;Mori, Kazungu & Panga 2015;Dell'Anno, AnaMaria & Balele, 2018;Munishi & Casmir, 2019;Munishi & Kirumirah, 2020a;Munishi & Kirumirah, 2020b). Evidence further shows that, the informal sector has played and still plays major role of employment and earnings for rapidly growing populations adding that from 1985 to 2010, the population bracket of 15-24 years of age doubled in the African and as a result urban informal trade almost tripled thanks to the less cumbersome regulations and taxation (Mgeni & Nayak, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Emezi et al (2021) posit the outcomes of positive and significant relationship which exists between founder's entrepreneur leadership style and SMEs survival. Mgeni's (2015) study results indicated a strong and impactful relationship between founder's entrepreneurial leadership style and SME performance (Mgeni & Nayak, 2015). Naushad's (2021) study outcome indicated that founder's entrepreneurial leadership style is a crucial device for owners/managers of the SMEs segment who aim to advance the responsibilities efficacy and circumstantial performance.…”
Section: Literature Review and Hypotheses Development Smes Internal D...mentioning
confidence: 96%